2018
DOI: 10.1186/s12884-018-2002-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum progesterone distribution in normal pregnancies compared to pregnancies complicated by threatened miscarriage from 5 to 13 weeks gestation: a prospective cohort study

Abstract: BackgroundProgesterone is a critical hormone in early pregnancy. A low level of serum progesterone is associated with threatened miscarriage. We aim to establish the distribution of maternal serum progesterone in normal pregnancies compared to pregnancies complicated by threatened miscarriage from 5 to 13 weeks gestation.MethodsThis is a single centre, prospective cohort study of 929 patients. Women from the Normal Pregnancy [NP] cohort were recruited from antenatal clinics, and those in the Threatened Miscarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 30 publications
5
42
0
2
Order By: Relevance
“…As far as we know, most studies suggested that serum progesterone levels were associated with pregnancy outcome, especially in the first trimester. Serum progesterone in abortion patients was generally lower than that in continuing pregnancy [10][11][12][13][14]. In our study, a negative correlation between serum progesterone and early pregnancy failure was further described.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…As far as we know, most studies suggested that serum progesterone levels were associated with pregnancy outcome, especially in the first trimester. Serum progesterone in abortion patients was generally lower than that in continuing pregnancy [10][11][12][13][14]. In our study, a negative correlation between serum progesterone and early pregnancy failure was further described.…”
Section: Discussionsupporting
confidence: 59%
“…Covariates. The selection of covariates in this study was mainly based on previous studies which researched the relationship between progesterone and pregnancy outcome [10][11][12][13][14][17][18][19][20][21][22]. Therefore, patients' basic demographics (age, height, weight, smoking history, drinking history, and marital status), obstetric history (times of gestity, parity, and abortion), and clinical information (gestational week, progesterone, ÎČ-HCG, medical history, and use of progesterone) were collected.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…P4 is essential for the establishment and maintenance of pregnancy as evident by the fact that administration of the P4-receptor antagonist Mifepristone (RU486) results in cessation of pregnancy (Couzinet et al 1986). Furthermore, lowered circulating levels of P4 have been associated with several pregnancy complications (Arck et al 2008, Okabe et al 2014, Ku et al 2018, and therapeutic use of P4 in pregnancy has been shown to reduce the risk of preterm birth in certain risk groups (Jarde et al 2019). In general, pregnancy hormones are believed to suppress maternal alloresponses while promoting fetal tolerance (Schumacher et al 2014).…”
Section: Endocrine Regulation Of Immune Cells During Pregnancymentioning
confidence: 99%